Daily practice and prognostic factors for pneumonia caused by methicillin-resistant Staphylococcus aureus in Japan: A multicenter prospective observational cohort study. Issue 2 (February 2020) - Miyazaki, Taiga; Yanagihara, Katsunori; Kakeya, Hiroshi; Izumikawa, Koichi; Mukae, Hiroshi; Shindo, Yuichiro; Yamamoto, Yoshihiro; Tateda, Kazuhiro; Tomono, Kazunori; Ishida, Tadashi; Hasegawa, Yoshinori; Niki, Yoshihito; et al.
Abstract: Pneumonia caused by methicillin-resistant Staphylococcus aureus (MRSA) is associated with poor clinical outcomes. We surveyed clinical outcomes of MRSA pneumonia in daily practice to identify risk factors for the clinical failure and mortality in patients with MRSA pneumonia. This multicenter prospective observational study was performed across 48 Japanese medical institutions. Adult patients with culture-positive MRSA pneumonia were recruited and treated with anti-MRSA antibiotics. The relationships between clinical and microbiological characteristics and clinical outcomes at test of cure (TOC) or 30-day all-cause mortality were analyzed. In total, 199 eligible patients, including nursing and healthcare-associated pneumonia (n = 95), hospital-acquired pneumonia (n = 76), and community-acquired pneumonia (n = 25), received initial treatment with anti-MRSA agents such as vancomycin (n = 135), linezolid (n = 36), or teicoplanin (n = 22). Overall clinical failure rate at TOC and the 30-day mortality rate were 51.1% (48/94 patients) and 33.7% (66/196 patients), respectively. Multivariable logistic regression analyses for vancomycin-treated populations revealed that abnormal white blood cell count (odds ratio [OR] 4.34, 95% confidence interval [CI] 1.31–14.39) was a risk factor for clinical failure and that no therapeutic drug monitoring (OR 3.10, 95% CI 1.35–7.12) and abnormally high C-reactive protein level (OR 3.54, 95% CI 1.26–9.92) were risk factors for mortality. In conclusion, this study provides evidence that majority of MRSA pneumonia patients are initially treated with vancomycin in Japan, and the absence of therapeutic drug monitoring for vancomycin is significantly associated with the mortality in patients with MRSA pneumonia.